Influence of Nonvisual Secondary Tasks on Driver's Pedestrian Detection - Iwasaki, Hirotoshi; Yoshizawa, Akira (International journal of cognitive informatics & natural intelligence, 2015)
The most frequent type of fatal traffic accident is caused by “aimless driving” in Japan. In many cases the victims are pedestrians on straight roads, where there are usually fewer objects drivers need to pay attention to than at intersections. In this study, the authors investigate driver gazing for detecting pedestrians in such situations. To make subjects seem “aimless,” they gave them nonvisual secondary tasks of four difficulty levels while they tried to watch pedestrians and press a key to answer their moving direction. The result indicated that even nonvisual tasks influence eye movement and the subjects fail to react properly.